Perceived Poor Quality of Care for Cardiac Patients in Nigeria: The Need to Optimize the Structure and Process of Care (African Journal of Biomedical Research, 2023)
Heart disease is a public health concern. Data on the quality of care given to patients with heart diseases in Nigeria are not readily available.  This study explored cardiac patients’ perception of the quality of care given to them in Nigeria. A mixed method design was used in this study. One hundred and twenty-six patients with heart diseases were recruited into this study through purposive sampling technique. A questionnaire adapted from previous studies was used to collect quantitative data from the patients. The data were analyzed using descriptive statistics of percentages and graphs.  Focus group discussion was used for qualitative data and was analyzed using content thematic analysis. The mean age of the patients was 55.31±15.64 years. Patients with heart diseases perceived different aspects of the structure and process of care as poor. Areas that were perceived as poor were poor teamwork among health care providers, prolonged waiting time, poor health record keeping, and inadequate information on treatment. Quality of care for cardiac patients in Nigeria was perceived as poor by patients. Process of care particularly teamwork in Nigeria is the major problem affecting quality of care for cardiac patients apart from structure of care